M137 Can Steroid Insensitivity In Copd Patients Be Restored Using Vitamin D?. (10th November 2014) - Mukherjee, D; Parekh, D; Dancer, R; Ungurs, M; Khiroya, H; Turner, AM
Abstract : Introduction: In many chronic diseases vitamin D has been proposed as an adjunctive anti-inflammatory therapy. Vitamin D up-regulates MKP1, thereby downregulating p38 phosphorylation and the NFKB inflammatory cascade (Zhang et al, J Immunol. 2012;188(5):2127–35). Steroids exert anti-inflammatory effects via this cascade, and exhibit synergy with vitamin D for some effects (Yu et al, Journal of the National Cancer Institute. 1998;90(2):134–41). Patients with COPD have chronic pulmonary inflammation, with upregulation of NFKB, yet do not exhibit a good response to steroids. Vitamin D therapy has been trialled in COPD patients, albeit with disappointing results (Lehouck et al, Annals of internal medicine. 2012;156(2):105–14). We hypothesised that COPD patients' inflammatory response would differ from health, and that vitamin D would exhibit synergy with steroids in vitro to improve this. Methods: PBMCs isolated from 10 COPD patients and 10 healthy control subjects were incubated with LPS, vitamin D, dexamethasone, a p38 MAPK inhibitor or combinations of these agents. Supernatants were harvested for TNF and IL6 measurements (ELISA). Results: LPS caused a marked rise in IL6 in both healthy controls (p = 0.044) and COPD patients (p = 0.008). IL6 reduction with vitamin D was only seen in health. IL6 reduction with addition of dexamethasone was not statistically significant (p = 0.636) in COPD. Combinations of agents failed to produce any additional benefit in both health and COPD. The response to vitamin D was heterogeneous; half of healthy subjects showed an anti-inflammatory response but in COPD only 12.5% of patients exhibited this. The difference in response rate was not significant (p = 0.120, Fishers exact test), though this may be due to low power. Similarly reduced response rate to dexamethasone was seen in COPD. Conclusion: Vitamin D does not enhance the anti-inflammatory effect of steroids. The anti-inflammatory effects of vitamin D are no different between COPD and health; variability of response may be one reason for lack of effect of vitamin D in clinical trials to date in COPD patients.